Semiconductor quantum dot lasers. - Hinzer, Karin. (University of Ottawa (Canada), 1998)
Stimulated emission in semiconductor quantum dot (QD) laser structures is demonstrated. Red-emitting, self-assembled QDs of highly strained InAlAs were grown by molecular beam epitaxy on GaAs substrates. Carriers injected electrically from the doped regions of separate confinement heterostructures thermalized efficiently into the zero-dimensional QD states, and stimulated emission at $\sim$707 nm is observed at 77 Kelvin with a threshold current of 175 milliamperes for a 60-$\mu$m by 400-$\mu$m broad area laser. A measured external quantum efficiency of $\sim$8.5% at low temperature with a peak power greater than 200 milliwatts demonstrate good size distribution and high gain in these high-quality QDs. At low temperatures, the lasing threshold currents are found to be more temperature insensitive than for two-dimensional quantum well (QW) lasers. At higher temperatures, the threshold current are governed mainly by the depth of the separate confinement region.
Keywords: Engineering, Electronics and Electrical.